Misconceptions in Electrochemistry among 11th- and 12th-Grade Students in Dire Dawa and Harari, Ethiopia: Causes, Effects, and Strategies - Melaku Masresha Woldeamanueal; Belay Sitotaw Goshu (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
Misconceptions in electrochemistry (ECT), such as believing electrons flow through the salt bridge, persist among students, influenced by didactic teaching, weak prior knowledge, and misleading resources. These errors vary across educational programs, impacting academic performance. This study aimed to examine school-specific ECT misconception rates and scores among 360 students from the Diploma in Design and Construction (DDC), Engineering and Operations Diploma (EOD), and Health and Social Sciences (HSS) programs, identifying contributing factors and proposing interventions. Data were collected via assessments and interviews (N = 30). Misconception prevalence (e.g., salt bridge error) and mean scores were analyzed for each group: DDC (65%, M = 26.2), EOD (75%, M = 24.1), and HSS (64%, M = 27.3). Interview responses highlighted didactic teaching (90–100%) and prior knowledge gaps (80–90%). Descriptive statistics and qualitative analysis informed findings. EOD showed the highest misconception rates (75%) and lowest scores (M = 24.1), linked to resource scarcity and 100% didactic teaching. DDC had moderate rates (65%) and scores (M = 26.2), tempered by 90% of didactic methods despite urban advantages. HSS exhibited the lowest rates (64%) and highest scores (M = 27.3), reflecting better teacher preparation, though 80% reported weak prior knowledge. ECT misconceptions correlate with teaching methods and resource availability, with EOD being the most affected. The groups encounter difficulties due to gaps in prior knowledge and passive teaching methods in HSS. Future research should test targeted interventions (e.g., labs, CCTs, teacher training) and expand longitudinal data collection to address these disparities effectively.